2017
DOI: 10.1115/1.4037396
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation on Heat Transfer Characteristics of Hot Surface by Using CuO–Water Nanofluids in Circular Jet Impingement Cooling

Abstract: In the present study, an experimental investigation has been carried out to analyze the heat transfer characteristics of CuO–water nanofluids jet on a hot surface. A rectangular stainless steel foil (AISI-304, 0.15 mm thick) used as the test surface is electrically heated to obtain the required initial temperature (500 °C). The distribution of surface heat flux on the target surface is evaluated from the recorded thermal images during transient cooling. The effect of nanoparticle concentration and Reynolds num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Gradeck et al in another experimental investigation with hot ferrous surface has reported that impurities in water or oil in water emulsion marginal increase the maximum surface heat flux as compared to the pure water jet. Moreover, the use of different surfactant or Nanofluid of certain concentration with water jet on hot steel surface increases the maximum surface heat flux in the range of 5–150% as compared to pure water jet . Therefore, addition of small amount of surfactant viz.…”
Section: Rewetting Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradeck et al in another experimental investigation with hot ferrous surface has reported that impurities in water or oil in water emulsion marginal increase the maximum surface heat flux as compared to the pure water jet. Moreover, the use of different surfactant or Nanofluid of certain concentration with water jet on hot steel surface increases the maximum surface heat flux in the range of 5–150% as compared to pure water jet . Therefore, addition of small amount of surfactant viz.…”
Section: Rewetting Parametersmentioning
confidence: 99%
“…In addition the nanoparticle deposition changes the number of micro‐cavities on the surface, thus, increases the surface area and roughness. All these effect consequently, leads to faster evaporation rate and higher surface heat flux . The surface heat transfer increase with the increase in nanoparticle concentration due to rise in effective thermal conductivity, thermal diffusion, Brownian motion of nanoparticles, and particle migration .…”
Section: Rewetting Parametersmentioning
confidence: 99%
“…This category of nanofluid was first proposed by Choi, in 1995, and is considered as the conventional form of nanofluids used, where a single type of nanoparticles is used to produce the suspension via different preparation methods [5]. It was reported by many authors that nanofluids of such category are superior in performance, due to having much more favourable thermophysical properties than their basefluid [51,[101][102][103][104].…”
Section: Single Materialsmentioning
confidence: 99%
“…Modak et al [101] experimentally investigated the heat transfer characteristics of copper oxide (CuO)/H 2 O nanosuspension impingement on a hot surface. During the preparational phase of the nanofluid, they found out that the optimum stability for the 0.15% and 0.60% volume concentration dispersion, at stationary condition, can be achieved for a period of 60 h at a pH value of 10.1 with a 0.2 wt% added sodium dodecyl sulfonate (SDS) surfactant.…”
Section: Ph Control Of Nanofluidsmentioning
confidence: 99%
“…Within past few years electronic industry developed vastly. Emerging technologies tends to increase demand for higher power densities in small dimensions [1][2]. Hence, performance of the equipment used for military or electronic industry needs high heat removal from small areas which directly increase its performance.…”
Section: Introductionmentioning
confidence: 99%